PENINGKATAN MOTIVASI BELAJAR IPA MELALUI MODEL PEMBELAJARAN SOMATIC AUDITORY VISUAL INTELLECTUAL PADA PEMBELAJARAN DARING - Hening Mahardika Jati; Mohammad Budiyanto; Enny Susiyawati (PENSA: E-JURNAL PENDIDIKAN SAINS, 2022)
This research aims to identify student’s learning motivation in online learning in science subjects through the SAVI (Somatic Auditory Visual Intellectual) model using vibration and wave materials. The research design used Pre-Experimental Design through One Group Pretest-Posttest Design The research respondents were 32 students of class VIII. Data collection techniques with questionnaires, observation of teacher and student activities, and evaluation tests. The questionnaire analysis technique uses a Likert scale which is calculated to increase studen’t motivation using the N-Gain test and is interpreted into the N-Gain category. Analysis of student activities using observation sheets which are interpreted into the criteria for student activity scores, and analysis of evaluation tests. Through the observation sheet, it can be seen from the students' activities are classified as very good after using the SAVI learning model. The results showed that students' learning motivation increased by 78.16 (N-Gain category: high) with 23 students being highly motivated and 9 students being moderately motivated. The implementation of learning using the SAVI learning model is in the very good category. Classical completeness reached 81.25%. Thus, in general, the application of SAVI on vibration and wave material can be used as a reference by science teachers as a reference for increasing student motivation in SMPN 1 Ngadirojo, especially class VIII.